(untitled) (Research, Society and Development, 2021)
Botany is one of the areas of Biological Sciences that is concerned with studying the life of algae and plants. Endowed with many terms, this area is seen by many students as complex and tedious. In order to get around this problem, the present work has as main objective to facilitate and motivate the learning of students in the discipline of Biology, in high school, regarding the topics of structure and function of seeds and yours germination in angiosperms. Thus, the proposed activity, allows the student to work with simple and low-cost materials such as corn seeds (Zea mays L.) and beans (Phaseolus vulgaris L.), 5% Iodine solution and household utensils applied in the seed viability and germination. Thus, the practical activity in question, allows the teacher to approach and discuss with students not only the topics of Botany, but also subjects related to Biochemistry, Plant Physiology and even aspects related to Agronomy. In this way, the proposal of the experimental activity allows to promote greater interest of the students, facilitating its contextualization besides allowing the exploration on the side of the scientific experimentation.